2015 9th International Conference on E-Commerce in Developing Countries: With Focus on E-Business (ECDC) 2015
DOI: 10.1109/ecdc.2015.7156314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of e-CRM on customer loyalty (case study: Esfahan Branch's of Sepah Bank)

Abstract: In today's competitive world, success is very close relationship with customer loyalty towards the organization.In several studies have shown that increased communication with clients and maintaining relationships with themwill eventually pave the way to customer satisfaction and 10yalty;Especially commercial and service organizations such as banks seeking major improvements in the way of their progress and customers are the main driving of these organizations. Loyalty maybe the one of most important structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…E-CRM is handful in adding up value to the entire process of buying and selling of an organization, as it satisfies the diverse needs and wants of customers more efficiently than its competitors and thus makes them happy and loyal with the organization. Ultimately, organizations not only upsurge their revenue but also their business starts flourishing through the implementation of newfangled tools of E-CRM (Salehi, Kheyrmand, & Faraghian, 2015).Considering the above, E-CRM becomes extremely important especially in banking sector (Singh & Jain, 2017).Therefore, the purpose of this study is to find the relationship between service quality, loyalty and trust on the effectiveness of electronic customer relationship management in Pakistani banking industry.…”
Section: Introductionmentioning
confidence: 99%
“…E-CRM is handful in adding up value to the entire process of buying and selling of an organization, as it satisfies the diverse needs and wants of customers more efficiently than its competitors and thus makes them happy and loyal with the organization. Ultimately, organizations not only upsurge their revenue but also their business starts flourishing through the implementation of newfangled tools of E-CRM (Salehi, Kheyrmand, & Faraghian, 2015).Considering the above, E-CRM becomes extremely important especially in banking sector (Singh & Jain, 2017).Therefore, the purpose of this study is to find the relationship between service quality, loyalty and trust on the effectiveness of electronic customer relationship management in Pakistani banking industry.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Ata and Toker, 2012; Azila and Noor, 2011; Salehi et al, 2015) have suggested that numerous business benefits accrue from the implementation of e-CRM, which enhances customer satisfaction and loyalty. In the light of the aforementioned, this paper explores how commercial banks may use technology and e-CRM to manage customer relationships and achieve customer loyalty.…”
mentioning
confidence: 99%
“…CRM is vital to service quality and a quick response to market changes (Jamali, Moshabaki, Aramoon and Alimohammadi, 2013). Due to technological advances, the use of e-CRM as a marketing paradigm is increasing (Bahrami, Ghorbani and Arabzad, 2012; Thuo, Kibera, K'Obonyo and Wainaina, 2011), and it is used as a strategy to enhance organizational flexibility (Dubihlela and E-CRM is defined as 'technology-centred' relationship marketing and ensuing advantages, incorporating traditional customer relationship management (CRM) tactics and e-business market place applications used by an organization to maintain customer relations (Dubihlela and Khosa, 2014; Harrigan, Ramsey and Ibbotson, 2012; Keshvari, 2012; KimSoon and Zulkifli, 2012; Salehi et al, 2015). Webbased technologies use the Internet to enable organizations to attract new customers, analyze their preferences and behaviors, customize support services while increasing services and value benefits, retain customers, and craft tactics to encourage loyalty (Ata and Toker, 2012).…”
mentioning
confidence: 99%
“…Although there is a large body of literature on BI's methods, tools, impact, success factors, etc., surprisingly little is known about how companies are actually drawing on BI in their day-to-day CRM. While there are studies that look into the application of BI in banks' CRM activities [e.g., 7,8], no study that we are aware of deals specifically with the usage of BI in database marketing processes. Likewise, knowledge about insurance companies' BI practices in CRM is sparse, despite the fact that the companies strongly depend on data analyses in order to offer their highly complex and individual products.…”
Section: Introductionmentioning
confidence: 99%